Error Analysis in the Descriptive Text Writing of Vocational High School Students - Ratnaningsih, Sita; Azizah, Azizah (Dinamika Ilmu, 2019)
English is one of the subjects that has been studied at the elementary to secondary level for many years in Indonesia. One area that must be studied is technical writing skills in English. In the technical writing process in English, there are still many mistakes made by students in Indonesia. So it is very necessary to recognize some common mistakes made by students, to help them improve their teaching and learning strategies in English and improve their learning outcomes. Therefore, this study aims to investigate errors in English technical writing of students at secondary vocational level and the factors that cause these errors. This study focused on errors made by the eleventh grade students of State 10 Vocational High School Jakarta, in their written descriptive text. A total of 30 students were the subjects of this study and they were asked to write descriptive texts. Data is analyzed based on Procedure Analysis This descriptive qualitative study explains and investigates student errors in writing the technique and the causative factors. Research shows that the typical mistakes students make in their writing: the highest place is capitalization with 60 errors (14.67%) and the lowest place is sentence 3 error (0.73%). According to a typical error, the author found the source of the error. The highest place is transfer between languages with 172 errors (42.05%) and the lowest place is a communication strategy with 49 errors (11.98%).